Revealing Microbiome Structure and Assembly Process in Three Rhizocompartments of Achyranthes bidentata Under Continuous Monoculture Regimes - Wang, Juanying; Wu, Hongmiao; Wu, Linkun; Liu, Ye; Letuma, Puleng; Qin, Xianjin; Chen, Ting; Rensing, Christopher; Lin, Sheng; Lin, Wenxiong (Frontiers in Microbiology, 2021)
The complex composition and interaction of root-associated microbes are critical to plant health and performance. In this study, we presented a detailed characterization of three rhizocompartment (rhizosphere, rhizoplane and root) microbiomes of A. bidentata under different years of consecutive monoculture by deep sequencing in order to determine keystone microorganisms via co-occurrence network analysis. The network analysis showed that multiple consecutive monoculture (MCM, represented 5Y and 10Y) soils generated some distinct beneficial bacterial taxa such as Bacillus, Fictibacillus, Bradyrhizobium, Shinella and Herbaspirillum. For fungi, Mortierella substituted for Fusarium in occupying an important position in different rhizocompartments under A. bidentate monoculture. Quantitative PCR analysis confirmed a significant increase in Bacillus, Pseudomonas and Burkholderia spp.. The results of the inoculation assay showed that addition of beneficial bacteria Bacillus subtilis 74 and Bacillus halodurans 75 significantly increased the root length and fresh weight of A. bidentata. Furthermore, three types of phytosterones, as the main allochemicals, were identified both in the rhizosphere soil and in culture medium under sterile conditions by LC-MS/MS. When looking at in vitro interactions, it was found that phytosterones displayed a positive interaction with dominant beneficial species (Bacillus amyloliquefaciens 4 and B. halodurans 75) and had a negative effect on the presence of the pathogenic fungi F. solani and F. oxysporum. Overall, this study demonstrated that consecutive monoculture of A. bidentata can alter the bacterial and fungal community by secreting root exudates, leading to recruitment of beneficial microbes and replacement of plant-specific pathogenic fungi with plant beneficial fungi.